2–6 GHz GaN distributed power amplifier MMIC with tapered gate‐series/drain‐shunt capacitors. Issue 5 (10th March 2016) - Bae, Kyung‐Tae; Kim, Dong‐Wook
ABSTRACT: In this article, using a 0.25 μm GaN HEMT process, we present a 2–6 GHz GaN two‐stage distributed power amplifier MMIC that utilizes tapered gate series capacitors and nonuniform drain transmission lines with tapered shunt capacitors to simultaneously obtain a linear gain enhancement and optimum load line for each transistor. By using well‐derived equations to provide each transistor with the optimum load impedance and to tune the phase delay between the input and output transmission lines, the nonuniform distributed power amplifier is designed for second‐stage amplification, and satisfactory performance is demonstrated. The phase balance and tapering of the gate series capacitors have a role in improving the linear gain of the two‐stage amplifier. The measured data show a linear gain of 22 ± 1 dB, an input/output return loss of more than 15 dB, saturated output power of 41.2–43.1 dBm under a continuous‐wave mode, and a power‐added efficiency of 18–22% from 2 to 6 GHz which are very competitive values compared with previous works. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:456–465, 2016.